THE PROVISION OF UNSECURED PEOPLE'S BUSINESS CREDIT (KUR) BASED ON LAW NO. 10 OF 1998 (STUDY AT PT. BANK BRI PULO BRAYAN BRANCH UNIT I) - Suhaila Zulkifi; Naomi Christine; Steven Lim; Wilfredo Leeson (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
One of the attractive services for the MSME group is the existence of one of the banking services offered by PT. Bank BRI Pulo Brayan Branch Unit I Medan, namely the People's Business Credit (KUR) based on the Minister of Finance Regulation Number 135/PMK.05/2008 concerning the People's Business Credit Guarantee Facility (KUR). However, it is important to note that the implementation of Unsecured KUR has a high degree of risk, so that countermeasures are needed to avoid the occurrence of non-performing loans (NPL). The research method used is normative-empirical legal research. Normative research is carried out and based on written provisions or other legal materials, while empirical research is carried out with a sociological approach obtained from primary data whose samples are directly from the community as the first source through field research. The activity of providing Unsecured KUR by PT. Bank BRI Pulo Brayan Branch Unit 1 Medan is based on a legal agreement that has legal consequences by adhering to the Pacta Sunt Servanda principle by applying the 5C+7P+3R principle which aims to prevent non-performing loans (Non Performing Loans) in the future.